The empire at the end of time identity and reform in late medieval German prophecy - Kneupper, Frances Courtney (New York, NY Oxford University Press, 2016)
Context -- Audience and reception -- Individual prophecies of late medieval German-speaking Europe -- The Gamaleon prophecy -- The letter of Brother Sigwalt -- The Auffahrt Abend prophecy -- The Wirsberger letters -- Themes in late medieval German prophecy -- The church and clergy in prophetic thought -- German identity in prophetic thought
ContextAudience and reception -- Individual prophecies of late medieval German-speaking Europe -- The Gamaleon prophecy -- The letter of Brother Sigwalt -- The Auffahrt Abend prophecy -- The Wirsberger letters -- Themes in late medieval German prophecy -- The church and clergy in prophetic thought -- German identity in prophetic thought.
Literaturverzeichnis: Seite 231-246
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Eschatology -- History of doctrines -- Middle Ages, 600-1500; Nationalism -- Germany -- History; Group Identity -- Germany -- History; Eschatology -- History of doctrines -- Middle Ages, 600-1500; Nationalism -- History -- Germany; Group Identity -- History -- Germany